Basal body structure in Trichonympha. Issue 1 (December 2016) - Guichard, Paul; Gönczy, Pierre
Abstract Trichonympha is a symbiotic flagellate of many species of termites and of the wood-feeding cockroach. Remarkably, this unicellular organism harbors up to over ten thousand flagella on its surface, which serve to propel it through the viscous environment of the host hindgut. In the 1960s, analysis of resin-embeddedTrichonympha samples by electron microscopy revealed that the basal bodies that give rise to these flagella are exceptionally long, with a proximal, cartwheel-bearing, region some 50 times longer than that of regular centrioles. In recent years, this salient feature has prompted the analysis of the 3D architecture ofTrichonympha basal bodies in the native state using cryo-electron tomography. The resulting ~40 Å resolution map of the basal body proximal region revealed a number of novel features that may be conserved in centrioles of other systems. These include proximal–distal polarity of the pinhead structure that links the cartwheel to centriolar microtubules, as well as of the linker between the A and the C microtubules. Moreover, this work demonstrated that the cartwheel is made of stacked ring-like structures that likely each comprise 18 molecules of SAS-6 proteins.